If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 2y = 3(2x + 3x) Combine like terms: 2x + 3x = 5x 2x + 2y = 3(5x) Remove parenthesis around (5x) 2x + 2y = 3 * 5x Multiply 3 * 5 2x + 2y = 15x Solving 2x + 2y = 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 2x + -15x + 2y = 15x + -15x Combine like terms: 2x + -15x = -13x -13x + 2y = 15x + -15x Combine like terms: 15x + -15x = 0 -13x + 2y = 0 Add '-2y' to each side of the equation. -13x + 2y + -2y = 0 + -2y Combine like terms: 2y + -2y = 0 -13x + 0 = 0 + -2y -13x = 0 + -2y Remove the zero: -13x = -2y Divide each side by '-13'. x = 0.1538461538y Simplifying x = 0.1538461538y
| 1.2x+3.4=2.45x-1.6 | | 8+2(4x+11)=54 | | 8+2(4x*11)=54 | | 2x=2*0.1557 | | (x/2)-(x/5)=1 | | F(x)=7x-3xfind(-2) | | 2x+11=100 | | 7-5x=x | | F(x)=7x-3x | | x+7=7x-17 | | 6x+2-3x=1 | | a+b^3= | | a/4=8=13 | | 2x/0.2-x=7.03 | | (x/2)-(x/5) | | 4x-12=10x | | 2(x+3)-11=x+5 | | 4x3/8 | | 2x+14=3x+2 | | t=2t-3(1-t) | | 4x+28=2x-1 | | a(1-x)=2ax+3-2a | | 4x-28=5x-40 | | 2(3x-5)+7=33 | | 3w-4=17 | | log16x=5/2 | | ax=a-b+bx | | -5(x-2)=40 | | -2x=1/7 | | 3u-1=14 | | 4x^3+2x^2+(-8x)+3=0 | | C=7n+2(n-1) |